Menelusuri Makna Keuntungan dibalik Pelaksanaan Budaya Tumbilotohe: Studi Etnometodologi Islam - Mohamad Anwar Thalib (Eastasouth Institute, 2022)
This study uses an Islamic paradigm with an Islamic ethnomethodology approach. Based on the study's results, the researchers concluded that there were four meanings of profit by the organizing committee of the Tumbilotohe activity. The first the benefits of happiness. The administrators interpret profit as a feeling of joy because they have succeeded in bringing crowds and entertainment to the local community through the implementation of tumbilotohe. Both gain inner satisfaction. The administrators interpret profits as inner satisfaction because the plan for organizing the Tumbilotohe culture has been successfully carried out smoothly and lively; besides that, this activity is an achievement for the committee because it was the first time they were able to organize an action on a large scale. Third, spiritual gain. The implementation of this activity is interpreted as a spiritual benefit because the activity fosters gratitude to the Creator. Fourth, the advantages of preserving culture.